Methods of Psychological Training of the Future Teacher of Music to Concert Performances - Jingheng, Geng (Pedagogical Discourse, 2014)
The article describes the methods of psychological training of the future teacher of music for concert performances as a special type of musical performance. Live performance is one of the basic regularities of musical activities and calls for the mobilization of efforts of the performer. The methods by which increases psychological stabilityof the artist during the live performance, have been studied. The difference of optimal concert state of the artist is the following components: emotional training, mental training, physical training. It is noted that it was the excitement of the stage of the artist - as one of the major psychological problems of the future music teacher, who performs vocal work in public. The stages of situational training are studied. In the first stage the artist dives into autogenous condition (immersion method in autogenous condition), in the second - figurative painting of a concert performance (method of singing in front of an imaginary audience) is studied.